Permeation mechanisms of hydrogen peroxide and water through plasma membrane intrinsic protein aquaporins - Chevriau, Jonathan; Zerbetto De Palma, Gerardo; Jozefkowicz, Cintia; Vitali, Victoria Andrea; Canessa Fortuna, Agustina; Ayub, Nicolás Daniel; Soto, Gabriela Cynthia; Bienert, Gerd Patrick; Zeida, Ari; Alleva, Karina Edith (Portland Press, 2025)
Hydrogen peroxide (H2O2) transport by aquaporins (AQP) is a critical feature for cellular redox signaling. However, the H2O2 permeation mechanism through these channels remains poorly understood. Through functional assays, two Plasma membrane Intrinsic Protein (PIP) AQP from Medicago truncatula, MtPIP2;2 and MtPIP2;3 have been identified as pH-gated channels capable of facilitating the permeation of both water (H2O) and H2O2. Employing a combination of unbiased and enhanced sampling molecular dynamics simulations, we investigated the key barriers and translocation mechanisms governing H2O2 permeation through these AQP in both open and closed conformational states. Our findings reveal that both H2O and H2O2 encounter their primary permeation barrier within the selectivity filter (SF) region of MtPIP2;3. In addition to the SF barrier, a second energetic barrier at the NPA (asparagine-proline-alanine) region that is more restrictive for the passage of H2O2 than for H2O, was found. This behavior can be attributed to a dissimilar geometric arrangement and hydrogen bonding profile between both molecules in this area. Collectively, these findings suggest mechanistic heterogeneity in H2O and H2O2 permeation through PIPs.